2022
DOI: 10.3390/genes13081298
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Loci for Type 2 Diabetes in the Ethnically Endogamous Indian Sindhi Population: A Pooled Blood Genome-Wide Association Study

Abstract: Type 2 diabetes (T2D) is a complex metabolic derangement that has a strong genetic basis. There is substantial population-specificity in the association of genetic variants with T2D. The Indian urban Sindhi population is at a high risk of T2D. The genetic basis of T2D in this population is unknown. We interrogated 28 pooled whole blood genomes of 1402 participants from the Diabetes In Sindhi Families In Nagpur (DISFIN) study using Illumina’s Global Screening Array. From a total of 608,550 biallelic variants, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This study utilized nationwide data, including a large number of participants (about 60,000). Several studies have previously suggested that some genes were genetically associated with metabolic disease [ 32 , 33 ]. On the other hand, we found gene-related SNPs that are more vulnerable to MI, especially in the group with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized nationwide data, including a large number of participants (about 60,000). Several studies have previously suggested that some genes were genetically associated with metabolic disease [ 32 , 33 ]. On the other hand, we found gene-related SNPs that are more vulnerable to MI, especially in the group with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF385 is one of the top expressed genes that defines β-cells in snRNAseq, as we have previously reported (17). Importantly, Gene-Wide Association Studies have strongly associated ZNF385D gene variants with T2D onset (70,71) and forced expression of ZNF385D together with retinoic acid receptor β ( RARB ) and Growth Arrest Specific 7 ( GAS7 ) genes in non-diabetic human islets leads to the appearance of a T2D-β-like phenotype in these islets (72). Interestingly, ZNF385D expression occurs mostly in the snRNA-seq dataset (pre-mRNA).…”
Section: Discussionmentioning
confidence: 99%
“…The TTN gene in the skeletal muscle and has been associated to cardiac serum proteins and fractal structure of the heart, as well as T2DM and nephron-related variables, such glomerular filtration rate (65)(66)(67). While gene PI16, DPY6, FRMD4A and CROCC have not been reported to be associated with nephropathy, they have been identified in T2DM (53,68) and obesity-related traits (69,70). PPP1R3A gene is associated with T2DM and plays a crucial role in glycogen synthesis in the tubules of the kidney, leading to diabetic nephropathy.…”
Section: Nephropathy Complicationsmentioning
confidence: 99%